Perspektif Mahasiswa terhadap Implementasi Problem Based Learning dalam Mata Kuliah Pengantar Ekonomi Makro - Anita Susanti; Irsa Nur Azizah Heryani; Ariska Azzahara; Arindra Putera Utama4; Buyung Firmansyah (FKIP, Universitas Palangka Raya, 2025)
This research was conducted because of the findings that show that students still lack the ability to solve problems, which can be seen from the tendency of students who are passive in answering questions from lecturers. The purpose of this research is to find out how the views or perspectives of students of the Faculty of Economics and Business Education, Universitas Pendidikan Indonesia regarding the application of problem-based learning methods in macroeconomics courses. The research was conducted using qualitative methods and interviews as a technique in collecting data. The results of this research show that students feel that their abilities are growing with the application of problem-based learning methods. For example, in personal abilities such as to improve problem solving skills and also in critical thinking. Then to improve interpersonal skills such as collaboration and interaction. In addition, there is an increase in the process of student reflection on a problem. Therefore, the problem-based learning method is very important to be applied and the support of educators is needed to streamline its application.